Clinical features of a case with trisomy 10q and monosomy 3p resulting from a maternal balanced translocation - Mahjoubi, Frouzandeh; Akbari, Mohammad Taghi; Babamohammadi, Gholamreza (Journal of Pediatric Neurology, 2008)
Here we describe clinical and cytogenetic data on 2-year-old female child with partial trisomy for the distal part of the long arm of chromosome 10 (10q22–>qter) and a concomitant monosomy 3(p25–>pter) as a result of a maternal balanced reciprocal translocation. Her karyotype was ascertained as 46,XX,der(3)t(3;10)(p25;q22). The father had normal karyotype. The mother had an apparently balanced translocation involving chromosome 3 and 10 [46,XX,t(3;10)(p25;q22)]. This is the second reported case of partial trisomy 10q and partial trisomy 3p. Clinical features of this case and a few published cases will be reviewed briefly.
Keywords: Trisomy 10q; monosomy 3p